Issues of analysis of development and assessment of the current situation in the tax field - Avazov Shodiyor Jumanazarovich (Genius Journals, 2024)
In this article, the new development strategy in our republic is to ensure the effectiveness of the tax-budget system. Tax policy plays a very important role in the economic policy of any country. The tax policy is closely related to other economic policies of the state and influences them. Correct development of tax policy and determination of its strategic and tactical directions is a very urgent and complex process
Keywords: Tax; tax attitudes; tax policy; tax policy strategy